Maintenance of peripheral venipuncture in children: perspectives of nursing professionals and companions (Research, Society and Development, 2020)
The professional/child/companion triad experiences, experiences and shares everyday situations about information and care practices regarding the maintenance of peripheral venipuncture make up a socially constituted group capable of representing the procedure as a socially shared object that need to be understood for an appropriate therapy. The general objective was to describe comparatively the social representations elaborated by nursing professionals and companions of hospitalized children about the maintenance of infantile peripheral venipuncture and how to triangulate structural and procedural approaches to social representations. Qualitative research outlined in the Theory of Social Representations. Collected sociodemographic data, applied the technique of free evocation of non-hierarchical words and individual interviews in depth, recorded, from guiding questions. Data analysis was performed according to the representational structure and content. All ethical and legal aspects of research involving human beings were complied with (Opinion No. 2,543,592). 22 nursing professionals and 118 companions participated. Representations for professionals about maintaining venipuncture in a child involved technical behaviors (reified knowledge) and, for companions, feelings of sadness and appreciation of their need (meanings). The need for reflections on the perspective of both regarding the maintenance of venipuncture in hospitalized children was evidenced in a less technical perspective and that considers the feelings and behaviors of the family-child dyad.